Shifting Fatherhood and Gender: Negotiating Power and Sexuality in Yoruba - Oluwasola Daniels (Yoruba Studies Review, 2022)
Indeed, Yorùbá is one of the vastly researched ethnics in Africa, but all the sub-groups, like Àkókó, are not sufficiently known in scholarship. Thus, with specific focus on Àkókó, this paper discusses gender in pre-colonial marital practices. It argues that while some of these practices made fatherhood fluid and accrued uncommon agency to women, others framed women in taboo and sexuality. The central contribution of this paper is that as a study in gender, it brings the discourse within the framework of shifting fatherhood and sexuality in Yorùbá. The study is approached from historical perspective with the methodology of narration and critical analysis of data. This research uses inter-disciplinary approach like ethnography to have full grasp of the marital dynamisms. In all, non-homogenization of history is crucial to understand hierarchies of power that shaped woman history and gender in Yorùbá.